Pengaruh Digital Marketing terhadap Minat Calon Mahasiswa Baru untuk Berkuliah di Universitas Prima Indonesia (UNPRI) - Palma Juanta; Arini Balqis; Abil Febrian Panggabean; Enjel Srimelda Damanik (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
This study examines the influence of digital marketing on the interest of prospective new students in enrolling at Universitas Prima Indonesia (UNPRI), Medan. Digital marketing has become a critical promotional channel for higher education institutions competing for Generation Z applicants who rely heavily on social media, websites, and online advertising. A quantitative associative (causal) design was used, employing a closed questionnaire with a four-point response scale (A-D) distributed to 70 respondents who had encountered information about UNPRI through digital media. Data were analyzed using Pearson product-moment validity testing, Cronbach's Alpha reliability testing, simple linear regression, and a partial t-test with the aid of SPSS. The results show that all eleven questionnaire items were valid (r-count > r-table = 0.235) and both research variables were reliable (Cronbach's Alpha above 0.60). The regression equation obtained was Y = 12.45 + 0.68X, indicating a positive relationship between digital marketing and student interest. The partial t-test produced a t-count of 5.231 (t-table = 1.995; sig. = 0.000 < 0.05), so H1 was accepted: digital marketing has a significant positive effect on the interest of prospective new students in choosing UNPRI. These findings suggest that UNPRI should continue to strengthen the quality of its social media content, website information, digital advertising, and responsiveness toward prospective students, particularly Generation Z applicants.